SOCIOLOGY 355: POLITICS AND SOCIETY - Bird, Donna (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course provides an overview of political sociology, the study of power and power structures at all levels of society. Your active participation in class, attention to the readings and engagement in group and individual learning activities will enable you to achieve familiarity with many significant aspects of this subdiscipline and to apply them to your own life experiences.